Conveyor Control System in Automatic Brick Making - Prasetyo, Aditya Apriyanto; Aji, Wahyu Sapto (Association for Scientific Computing Electrical and Engineering (ASCEE), 2020)
Brick is a building material that is still widely used by people today. Most of the small-scale brick-making industries print bricks in the traditional way. Of the problems encountered by adding a conveyor as a means of carrying soil that has been printed and then running through the conveyor to the brick makers to add security to the brick makers. The stages of the research were carried out by identifying the problem to produce data from the system to be made, then designing the concept for making the tool. In tool making, the most important components are conveyors, dc motors and PLCs as the main controls in running conveyors. This conveyor works to bring the dough quickly to the craftsmen so that the dough can be measured for the speed of time and the level of safety for the craftsmen. This research has succeeded in creating a